Identification of phenolics from miracle berry (Synsepalum dulcificum) leaf extract and its antiangiogenesis and anticancer activities - Ma, Fei-Yue; Zhang, Xiu-Mei; Li, Ya; Zhang, Ming; Tu, Xing-Hao; Du, Li-Qing (Frontiers in Nutrition, 2022)
Miracle berry is well known for its ability to convert sour foods to sweet. In this study, miracle berry leaf (MBL) extract was identified, and its anti-angiogenesis and anticancer activities were evaluated by using a zebrafish model and the MCF-7 xenograft mouse model, respectively. The result showed that 18 phenolic compounds in MBL extract were identified, mainly including quercetin and myricetin derivatives. The MBL extract showed low toxicity and high anti-angiogenesis activity, it significantly inhibited the subintestinal vein vessels development in zebrafish at very low concentration. Furthermore, the MBL extract treatment could promote the apoptosis of tumor cells and significantly inhibit the growth of MCF-7 xenograft tumor. In addition, the analysis of metabolites revealed that the MBL extract inhibited tumor growth by activating the metabolic pathways of unsaturated fatty acids and purines. Overall, the results of this study suggest that MBL extract can be used as a natural anticancer adjuvant in the fields of functional foods.